Study of the photovoltaic properties of Cs and Cl co-doped FAPbI3 based on first principles - Shangfen Huang; Haixia Li; Jun Liu; Jun Tao (Materials Research Express, 2023)
Formamidine lead iodide perovskite (FAPbI _3 ) is often used as a light-absorbing layer in solar cells to alleviate the energy crisis because of its good photovoltaic properties. However, its lack of stability is also an obstacle to the current development. It has been found that doping with different kinds of elements at different sites can enhance its stability and improve the photoelectric conversion efficiency of solar cells. In this study, the geometry, electronic structure, and optical properties of FA _1−x CsxPbI _3−y Cl _y were calculated using Cs and Cl co-doped with FAPbI _3 using first principles. The analysis revealed that the Goldschmidt factors of the doped system were between 0.962 and 0.974, indicating that the systems could maintain a stable perovskite structure and that the doped system had lower energy and a more stable structure. By calculating the energy bands, it was found that the doped ions have a more pronounced effect on the increase in the dispersion at the bottom of the conduction band than on the decrease in the dispersion at the top of the valence band of the system, and the reduction of the effective mass of carriers is more favorable for transport. As for the optical properties, the right amount of doping is favorable for the improvement of light absorption, whereas excess doping shortens the light absorption range and weakens the light absorption effect, in which FA _0.875 Cs _0.125 PbI _2.958 Cl _0.125 has the largest light absorption coefficient. It is shown that the photoelectric properties of FAPbI _3 can be effectively modulated by the co-doping with Cs and Cl, which can provide a theoretical reference for the precise preparation of more efficient solar cells.